-2x-107=133+6x

Simple and best practice solution for -2x-107=133+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-107=133+6x equation:


Simplifying
-2x + -107 = 133 + 6x

Reorder the terms:
-107 + -2x = 133 + 6x

Solving
-107 + -2x = 133 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-107 + -2x + -6x = 133 + 6x + -6x

Combine like terms: -2x + -6x = -8x
-107 + -8x = 133 + 6x + -6x

Combine like terms: 6x + -6x = 0
-107 + -8x = 133 + 0
-107 + -8x = 133

Add '107' to each side of the equation.
-107 + 107 + -8x = 133 + 107

Combine like terms: -107 + 107 = 0
0 + -8x = 133 + 107
-8x = 133 + 107

Combine like terms: 133 + 107 = 240
-8x = 240

Divide each side by '-8'.
x = -30

Simplifying
x = -30

See similar equations:

| (4-9i)(7-9i)= | | 14k+13=20 | | 4(c-2)=3(x-3) | | 4k+13=13 | | -133-2x=119-11x | | 7(m-4)=-29+7m | | z=(6+x)k | | -8(y+4)=6-7y | | n-20=n*6+15 | | 2x(2x+1)=3 | | mn-2n+7m-14= | | 3x-6=2x+17 | | 81x-100y^4=0 | | 24x^2-8x^2= | | 7(x+3)+5=-6(x-1) | | -(8x-3)-(3x-5)+11=-9(x-1)-(7x+8)+3 | | 8+4y=4 | | -2(4-3x)6x=10 | | 6(x-7)+6=3(x-6) | | 3x-17=5+2x | | -6(5-x)+1=3(x+2) | | 11x-3=5x+21 | | 0.16-0.01(x+2)=0.03(2-x) | | 4(n-12)=12(n-4) | | 125+m=725 | | 35=-2x-25 | | 4(n-12)=12(4-n) | | -4/5=-1/4-5/6q | | (9x-4)(5x+5)= | | X^2-8=9x | | -7(-4-4x)-6=1+7x | | 3(x-7)-4(2+x)=3 |

Equations solver categories